The Impact of Access To Finance on Firm Performance: Evidence from Microenterprises of Sri Lanka - Liyanage, M.L.D.C.J.; Morais, S.N.; Abeysinghe, S.; Wickramasinghe, C.N. (University of Jaffna, 2023)
Lack of access to finance constantly emerges as one of the most imperative and robust underlying factors restricting firm growth and performance. Even though there were many literatures found on global scale there is very limited research conduct in Sri Lankan context, especially on the microenterprise’s perspective. Therefore, the main purpose of this study to fulfill this gap and investigate the role of access to finance on the performance of microenterprises in Sri Lanka. The study followed positivism philosophy and a deductive approach. As survey strategy was chosen, a structured questionnaire was used as the data collection tool from a sample of 385 Sri Lankan microentrepreneurs. The author has developed hypothesis and test them using the SPSS software. The findings indicate that increased access to finance has positive effects on the growth of profit, sales, and asset base of the micro enterprises. However, its impact of access to finance on employment generation was weak. Further, the study confirms the assumption that employment generation within microenterprise sector is persistently low. This study contributed to the local body of literature by analyzing the different employment groups of microenterprises and their relationship to access to finance in Sri Lankan context.
Keywords: Access to Finance; Employment Generation; Firm Performance; JEL Classification : G32